2014
DOI: 10.3402/gha.v7.24194
|View full text |Cite
|
Sign up to set email alerts
|

Security and skills: the two key issues in health worker migration

Abstract: BackgroundMigration of health workers from Africa continues to undermine the universal provision of quality health care. South Africa is an epicentre for migration – it exports more health workers to high-income countries than any other African country and imports health workers from its lower-income neighbours to fill the gap. Although an inter-governmental agreement in 2003 reduced the very high numbers migrating from South Africa to the United Kingdom, migration continues to other high-income English-speaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 27 publications
2
52
1
Order By: Relevance
“…Deskilling and devaluing of overseas nurses has been reported in various studies [25, 29, 46, 62, 74]. Studies about these phenomena for migrant female physicians, however, are missing.…”
Section: Discussionmentioning
confidence: 99%
“…Deskilling and devaluing of overseas nurses has been reported in various studies [25, 29, 46, 62, 74]. Studies about these phenomena for migrant female physicians, however, are missing.…”
Section: Discussionmentioning
confidence: 99%
“…). Apply learned knowledge; be satisfied after graduation; be satisfied in remuneration; be appreciated as a nurse (Habermann & Stagge ). Maintain relationships; deal with the risk of ability declines; have the expected quality of life (Hendel & Kagan ). Maintain contact with relatives and friends (Nair & Webster ). Work in a safe country and in a safe environment, economically developed; where there is growth and trust; where there is respect between workers; and the possibility of working with skilled colleagues (Bidwell et al. ; Dywili et al. ); where the profession is respected; and where there are advanced technologies (Thompson et al.…”
Section: Methodsmentioning
confidence: 99%
“…d Maintain contact with relatives and friends (Nair & Webster 2012). e Work in a safe country and in a safe environment, economically developed; where there is growth and trust; where there is respect between workers; and the possibility of working with skilled colleagues (Bidwell et al 2014;Dywili et al 2013); where the profession is respected; and where there are advanced technologies (Thompson et al 2014). Then, the above-mentioned elements were analysed and transformed by researchers (AP, FM) into 45 items.…”
Section: Data Collectionmentioning
confidence: 99%
“…A study of South African health workers who had immigrated to the U.K., for example, found that those who had left to pursue academic opportunities were more likely to return to South Africa. Indeed, some had emigrated for the express purpose of gaining skills and expertise to apply in the South African health system (Bidwell et al, 2014).…”
Section: Stemming the Medical Brain Drain: A Personal Perspective On mentioning
confidence: 99%